2022
DOI: 10.1155/2022/2952531
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Sleep Quality and TCM Constitution Characteristics in 258 Outpatients: A Cross-Sectional Study Based on Outpatient Cases

Abstract: Objective. To explore the correlation between traditional Chinese medicine (TCM) constitutions and insomnia by studying the distribution characteristics of different TCM constitutions in an outpatient insomnia population. Methods. From November 2020 to March 2021, 258 patients in the outpatient department of the Traditional Medicine Department of Tongren Hospital were interviewed using some questionnaires (Athens Insomnia Scale and constitution of traditional Chinese medicine), and correlation analysis was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Another study has shown that Qi-deficiency was significantly associated with emotional, pain, and fatigue in SLE patients [ 46 ]. Moreover, Qi-deficiency constitution, Qi-depression constitution, and Blood-stasis constitution were all significantly associated with insomnia [ 47 ]. In addition, other studies have shown that Blood-stasis constitution was a risk factor for cognitive dysfunction [ 48 ], was strongly associated with the development of peripheral arterial disease in patients with type 2 diabetes mellitus [ 49 ], and may also be used as an early predictive diagnostic indicator for the development of coronary artery disease in patients with chest pain [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that Qi-deficiency was significantly associated with emotional, pain, and fatigue in SLE patients [ 46 ]. Moreover, Qi-deficiency constitution, Qi-depression constitution, and Blood-stasis constitution were all significantly associated with insomnia [ 47 ]. In addition, other studies have shown that Blood-stasis constitution was a risk factor for cognitive dysfunction [ 48 ], was strongly associated with the development of peripheral arterial disease in patients with type 2 diabetes mellitus [ 49 ], and may also be used as an early predictive diagnostic indicator for the development of coronary artery disease in patients with chest pain [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study underscores the significant influence of TCM constitution on the prevention and prognosis of insomnia, suggesting that the CCM scale score could act as a crucial predictive tool for determining the severity of insomnia. The uniquely powerful role of an individual’s constitution in TCM highlights its impact on overall physical and mental health, with a marked effect on susceptibility and severity of illnesses, including insomnia ( 17 ). By exploring the predictive capabilities of the CCM scale in relation to insomnia severity, we are not only poised to forge innovative links between TCM and modern sleep medicine, but also lay the foundation for the development of more comprehensive, personalized therapeutic strategies that emphasize the remarkable contributions of TCM constitution in managing and predicting insomnia, thus shaping its treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%